A Conceptual Analysis of the Semantic Use of Multiple Intelligences Theory and Implications for Teacher Education - Attwood, Adam I. (Frontiers in Psychology, 2022)
Gardner’s theory of multiple intelligences (MI) has been at the center of a long-running debate in educational psychology in terms of its generalizable validity. In this article, MI theory is discussed for a review of why and how MI theory may be contextually discussed for preservice teachers to learn about in their teacher education program. The semantic conceptual basis of intelligence in MI theory is discussed in comparison to learning styles theory with implications for the importance of the teaching of Universal Design for Learning (UDL) and related frameworks in teacher education curriculum.